NON-FINANCIAL FIRMS AND THE MAXIMIZING SHAREHOLDER VALUE STRATEGY IMPACTS OVER EMPLOYMENT IN BRAZIL - Attílio, Luccas Assis (2019)
This article investigates the maximizing shareholder value strategy for a sampleof non-financial publicly held companies between 1997 and 2013. It also estimates the latterimpact over employment on firms’ respective sectors of activity. In order to estimate sucheffects the Two-Stage Least Squares method was used, with support the Chain ReactionTheory. Results indicate that increases in shared dividends, via maximizing shareholdervalue strategy, have negative effects over the productive investment in which, by its turn,slow down the employment creation.